Osteoprotegerin: Relationship to Breast Cancer Risk and Prognosis - Geerts, Dirk; Chopra, Christina; Connelly, Linda (Frontiers in Oncology, 2020)
Osteoprotegerin (OPG) is a secreted member of the Tumor Necrosis Factor (TNF) receptor superfamily (TNFRSF11B), that was first characterized and named for its protective role in bone remodeling. In this context, OPG binds to another TNF superfamily member Receptor Activator of NF-kappaB Ligand (RANKL; TNFSF11) and blocks interaction with RANK (TNFRSF11A), preventing RANKL/RANK stimulation of osteoclast maturation and bone breakdown. Further studies revealed that OPG protein is also expressed by tumor cells and led to investigation of the role of OPG in tumor biology. An increasing body of data has demonstrated that OPG modulates breast tumor behavior. Initially, research was focused on OPG in the bone microenvironment as a potential inhibitor of RANKL-driven osteolysis. More recently, attention has shifted to include OPG expression and interactions in the primary breast tumor independent of RANKL. In the primary tumor, OPG may interact with another TNF superfamily member, TNF-Related Apoptosis Inducing Ligand (TRAIL; TNFSF10) to prevent apoptosis induction. Additional interest in OPG in breast cancer has been stimulated by the tumor-promoting role of its binding partner RANKL in association with BRCA1 gene mutations. We and others have previously summarized the functional studies on OPG and breast cancer (Weichhaus et al, 2015; Goswami et al, 2016). After basic research studies on the in vitro role for OPG (and RANKL) in breast cancer, the field now expands to assess the in vivo role for OPG by examining the correlation between OPG expression and breast cancer risk or patient prognosis. However, the data reported so far is conflicting, since OPG expression appears linked to both good and poor patient survival. In the current review we will summarize these studies. Our goal is to provide stimulus for further research to bridge the basic research findings and clinical data regarding OPG in breast cancer.